Irish immigrants in America : an interactive history adventure - Raum, Elizabeth (Capstone Press, 2008)
Describes the experiences of Irish immigrants upon arriving in America during the time of the Irish potato famine, revealing historical details about where they settled, the jobs they found, and the difficulties they faced.